Differential Activity of Coexisting Prochlorococcus Ecotypes - Thompson, Anne W.; Kouba, Kathleen (Frontiers in Marine Science, 2019)
The abundance and widespread distribution of the unicellular cyanobacterium Prochlorococcus is attributed to its extensive genetic diversity. At least twelve distinct clades, or ecotypes, of Prochlorococcus have been discovered so far, and follow distinct distribution patterns over horizontal and vertical gradients in the oligotrophic ocean. However, multiple ecotypes (and sub-ecotypes) of Prochlorococcus always coexist in varying proportions. While laboratory experiments and genomic analysis suggest that ecotypes contribute differently to biogeochemical cycles, no studies have tested the differential activity of coexisting ecotypes in natural assemblages of Prochlorococcus. Here, we performed DNA stable isotope probing (DNA-SIP) experiments in on-deck incubations of oceanic microbial communities with 13C-labeled bicarbonate to identify ecotypes actively assimilating carbon. In addition, we identified cells in G1 and G2 phases of the cell cycle to determine the ecotypes engaged in cell division. We found that closely related ecotypes and sub-ecotypes could exhibit differential activity in carbon assimilation and cell division. In the case of cell division, the most actively dividing ecotype was among the most abundant ecotypes. In the case of carbon assimilation, both a rare OTU and an abundant OTU were the most active. We discuss how intrinsic genomic characteristics, acclimation state, microbial interactions, and physical dynamics of the ocean could contribute to these patterns of activity. Together, these experiments suggest that Prochlorococcus community structure is an important facet of Prochlorococcus contributions to the ocean ecosystem that should be studied further to predict the influence of Prochlorococcus on global processes.